2003
DOI: 10.1177/000348940311200401
|View full text |Cite
|
Sign up to set email alerts
|

Central Facilitation of the Glottic Closure Reflex in Humans

Abstract: The sphincteric function of the larynx, essential to lower airway protection, is most efficiently achieved through strong reflex adduction by both vocal cords. We hypothesize that central facilitation is an essential component of a bilateral adductor reflex and that its disturbance could result in weakened sphincteric closure. Five patients during supraglottic laryngectomy underwent evoked response laryngeal electromyography under 0.5 and 1.0 minimal alveolar concentration (MAC) isoflurane anesthesia. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 9 publications
3
37
1
Order By: Relevance
“…This suggests that, under general anesthesia, the R1 component of the LAR may be the predominant contractile force. cR1 latencies were comparable to cR1 latencies reported by Sasaki et al and were 4 ms to 6 ms longer than previously reported iR1 responses in awake and anesthetized states, consistent with the additional time required for impulses to cross to the contralateral side of the brainstem. cR2 latencies in this series were within the range of R2 latencies noted for awake patients in prior studies The consistency of response latencies across all studies, despite different stimulation strategies and consciousness states, implies that TIVA anesthesia has minimal effect on conduction time of the reflex and attests to the robust nature of these responses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that, under general anesthesia, the R1 component of the LAR may be the predominant contractile force. cR1 latencies were comparable to cR1 latencies reported by Sasaki et al and were 4 ms to 6 ms longer than previously reported iR1 responses in awake and anesthetized states, consistent with the additional time required for impulses to cross to the contralateral side of the brainstem. cR2 latencies in this series were within the range of R2 latencies noted for awake patients in prior studies The consistency of response latencies across all studies, despite different stimulation strategies and consciousness states, implies that TIVA anesthesia has minimal effect on conduction time of the reflex and attests to the robust nature of these responses.…”
Section: Discussionsupporting
confidence: 89%
“…cR2 latencies in this series were within the range of R2 latencies noted for awake patients in prior studies The consistency of response latencies across all studies, despite different stimulation strategies and consciousness states, implies that TIVA anesthesia has minimal effect on conduction time of the reflex and attests to the robust nature of these responses. Regarding the strength of mucosal stimulus, the current range (3–8 mA) used in this study was comparable to that utilized by other authors, with no perioperative or postoperative complications noted in this or other studies …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our model, we propose that the iSLN projects to motor neurons of nucleus ambiguus through at least two synapses, the first within ipsilateral nucleus tractus solitarius, and the second likely within nucleus ambiguus ipsilaterally and contralaterally within the reticular formation in a manner supported by Sessle's observations. 26 In recent studies, it was suggested that the pig model has equivalent numbers of ipsilateral and contralateral interneurons,22 and that humans have 2 to 3 more contralateral interneurons compared to ipsilateral side 27. However, in our current study with canine model, the fact that the contralateral latency was about 2 msec longer than ipsilateral one leads us to suggest the presence of one more interneuron possibly in the reticular formation (Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…The late bilateral thyroarytenoid response occurred in awake humans but was rare in the anesthetized cat. A study of changes in the laryngeal closure response in patients at different anesthesia levels demonstrated that the bilateral response only occurred when the level of anesthesia was reduced (Sasaki, Jassin, Kim, et al, 2003). The late responses in the cat only occurred when ketamine was not administered demonstrating that this late component is a glutaminergic pathway (Ambalavanar, Purcell, Miranda, et al, 2002).…”
Section: Laryngeal Reflexesmentioning
confidence: 99%